Nursing Care For The Application of Combined Deep Breath Relaxation Techniques and Lavender Aromatherapy in Post-Prostatectomy Patients with Acute Pain Problems at RSUD Jendral Ahmad Yani Metro City - Malinda, Reni; Wardoyo, Eko; Sugiarto, Sugiarto (INDOGENIUS, 2025)
Background & Objective: The purpose of this study was to determine the effect of deep breath relaxation and lavender aromatherapy on reducing the pain scale of post-prostatectomy patients. Method: Descriptive type of research with a case study approach in multiple cases. Data collection methods using surgical nursing care assessment sheets and pain scale observation sheets using the Numeric Rating Scale. The study used 2 patients with the same criteria. Result: The results of this study are proven effectiveness in reducing pain intensity in both patients. There is a decrease between before and after being given deep breath relaxation techniques and lavender aromatherapy for 3 days, as evidenced by using the Number Rating Scale (NRS) score after being given deep breath relaxation techniques and lavender aromatherapy for 15 minutes for 3 days, the results showed a change in the pain scale in patient 1 and patient 2, with patient 1's pain scale from 6 to 3 and patient 2 from 5 to 2. Conclusion: Researchers advise nurses in overcoming pain with deep breath relaxation techniques and lavender aromatherapy as non-pharmacological therapy.